Comparative analysis of the trypanocidal activity and chemical properties of E-lychnophoric acid and its derivatives using theoretical calculations - A. F. C. Alcântara (Eclética Química, 2005)
E-Lychnophoric acid 1, its derivative ester 2 and alcohol 3 killed 100% of trypomastigoteblood forms of Trypanosoma cruzi at the concentrations of 13.86, 5.68, and 6.48 µg/mL, respectively.Conformational distribution calculations (AM1) of 1, 2 and 3 gave minimum energies for the conformersa, b, c, and d, which differ from each other only in the cyclononene ring geometry. Calculations (DFT/BLYP/6-31G*) of geometry optimization and chemical properties were performed for conformers of 1, 2,and 3. The theoretical results were numerically compared to the trypanocidal activity. Calculated valuesof atomic charge, orbital population, and vibrational frequencies showed that the C-4C-5 π-endocyclicbond does not affect the trypanocidal activity of the studied compounds. Nevertheless, the structure ofthe group at C-4 strongly influences the activity. However, the theoretical results indicated that the intraring(C-1 and C-9) and π-exocycle (C-8 and C-14) carbons of caryophyllene-type structures promotethe trypanocidal activity of these compounds.